Nurturing sport expertise: Factors influencing the development of elite athlete - Baker, J.; Horton, S.; Robertson-Wilson, J.; Wall, M. (Journal of Sports Science & Medicine, 2003)
The development of expertise in sport is the result of successful interaction of biological, psychological, and sociological constraints. This review examines the training and environmental factors that influence the acquisition of sport expertise. Research examining the quality and quantity of training indicate that these two elements are crucial predictors of attainment. In addition, the possession of resources such as parental support and adequate coaching are essential. Social factors such as cultural influences and the relative age effect are also considered as determinants of sport expertise. Although it is evident that environmental factors are essential to the acquisition of high levels of sport development, further research is clearly required. Although there is a wealth of information regarding the environmental and training factors that influence the acquisition and maintenance of expert performance, our understanding is far from complete. Future research is needed to address areas of limitation, such as the interaction between training and genetic predispositions or the balance between training stress and recovery. Further examinations of the resources that constrain the development of expertise are also essential. Current examinations from our laboratory with triathletes, ice-hockey players, soccer players and expert coaches are examining these and other issues.